1987
DOI: 10.1177/088626087002002003
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Measure for the Assessment of Anger and Aggression

Abstract: A brief, six-item measure was developed for the rapid screening and identification of anger and aggression levels in violence-prone men. Four studies were conducted to examine the reliability and validity of the measure using a clinical data base of 401 men. Analyses indicated a satisfactory degree of internal consistency, test-retest reliability, and a significant relationship between the brief measure and Buss-Durkee Hostility Inventory total scores. Significantly higher scores were observed for three types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 4 publications
0
42
0
5
Order By: Relevance
“…Unfortunately, however, the correlations between boredom and other negative emotions are accompanied by an overlap in several of their correlates and consequences. For example, boredom proneness predicts aggression (Dahlen et al, 2004), but so do frustration (e.g., Miller, 1941) and anger (Maiuro, Vitaliano, & Cahn, 1987). Furthermore, although empirical work has confirmed that boredom involves a sense of meaninglessness (Fahlman, Mercer, Gaskocski, Eastwood, & Eastwood, 2009;Van Tilburg & Igou, 2012), so do sadness and feelings of depression (Steger, Frazier, Oishi, & Kaler, 2006).…”
Section: How Does Boredom Compare To Other Emotions?mentioning
confidence: 99%
“…Unfortunately, however, the correlations between boredom and other negative emotions are accompanied by an overlap in several of their correlates and consequences. For example, boredom proneness predicts aggression (Dahlen et al, 2004), but so do frustration (e.g., Miller, 1941) and anger (Maiuro, Vitaliano, & Cahn, 1987). Furthermore, although empirical work has confirmed that boredom involves a sense of meaninglessness (Fahlman, Mercer, Gaskocski, Eastwood, & Eastwood, 2009;Van Tilburg & Igou, 2012), so do sadness and feelings of depression (Steger, Frazier, Oishi, & Kaler, 2006).…”
Section: How Does Boredom Compare To Other Emotions?mentioning
confidence: 99%
“…This study was designed to investigate relations among questionnaire scales of Anger and Aggression [Maiuro et al, 1987], Feelings and Acts of Violence [Plutchik and van Praag, 1990], REV [Mehrabian, 1996c], Emotional Empathic Tendency [EETS, Mehrabian and Epstein, 1972], and Balanced Emotional Empathy [Mehrabian, 1996b]. The EETS was one of the most widely used measures of emotional empathy in the literature [Chlopan et al, 1985;Mehrabian et al, 1988;Miller and Eisenberg, 1988].…”
Section: Studymentioning
confidence: 99%
“…Brief Anger-Aggression Questionnaire [Maiuro et al, 1987]. This scale consists of six items exemplified by: "When I get mad I say threatening or nasty things"; "When I really lose my temper, I am capable of hitting or slapping someone."…”
Section: Risk Of Eruptive Violence Scale (Rev)mentioning
confidence: 99%
See 1 more Smart Citation
“…El CBCA (Brief Anger Agression Questionnaire, Maiuro, Vitaliano & Cahn, 1987) es una medida de seis ítems para valorar los niveles de coraje (e.j., a veces siento que me toca la peor parte de la vida) y agresión (e.j., me pongo tan enojado(a) que golpeo, aviento, o pateo cosas). Los ítems son calificados en una escala que va de 0 (extremadamente improbable) a 4 (muy probable), con un total de calificaciones de 0 a 24 (la calificación de corte en 9 indica una probabilidad justa de descontrol por coraje o agresión).…”
Section: Le Grito a MI Niña(o) Por Tirar La Comida)unclassified